دور نظام التعليم عن بعد في تحقيق الإدارة الفعالة للوقت لدى طلبة كلية العلوم الاقتصادية والعلوم التجارية وعلوم التسيير بجامعة الجلفة - ثامري, أحلام; جوال, محمد السعيد; رابحي, مختار (جامعة الوادي - University of Eloued, 2023)
This study aimed to determine the extent of the impact of the distance education system on effective time management. One hundred questionnaires distributed to the respondents electronically were analyzed to reach this goal. Partial least squares structural equation modeling using smartPLS4 was used to test the study hypotheses. The study results found a positive relationship between distance education and effective time management through the two dimensions of the effectiveness of electronic content and distance education tools. In contrast, the students' ability dimension did not affect effective time management.
The role of the distance education system in achieving effective time management for students of the Faculty of Economics Commerce and Management Sciences in University of Djelfa
مقال
Keywords: نظام التعليم عن بعد ; إدارة الوقت ; الإدارة الفعالة للوقت